Natural Flavonoid Quercetin Enhances the Anti-inflammatory Effects of Aspirin in a Preeclampsia-like Rat Model Induced by Lipopolysaccharide - Chen, Dan; Yang, Shuangyan; Ding, Jie; Liu, Ailing (Current Molecular Medicine, 2023)
Background: Preeclampsia is a disorder of hypertension and proteinuria accompanied by abnormal inflammatory responses. Both aspirin and quercetin possess anti-inflammatory and anti-hypertensive properties. A low dose of aspirin is recommended for the prevention of preeclampsia in patients with preeclampsia history. Whether quercetin can enhance the effect of aspirin on preeclampsia remains elusive. Methods: Female Sprague-Dawley pregnant rats were treated with daily administration of aspirin, quercetin, or a combination of aspirin and quercetin and subsequently received lipopolysaccharides (LPS) injection to induce preeclampsia-like symptoms. The systolic blood pressure and proteinuria from all groups of rats were assessed. Results: Our results demonstrated that the combination of quercetin and aspirin exerted significantly stronger effects than aspirin alone on decreasing systolic blood pressure and proteinuria, reducing pro-inflammatory cytokine production, and inhibiting M1-type decidual macrophages polarization in an LPS-induced rat model of preeclampsia. Conclusion: This study suggested that quercetin may serve as an excellent supplement to aspirin in preventing or treating patients with preeclampsia.
Keywords: lipopolysaccharides